ANALISIS PENDAPATAN ANGGOTA DAN NON-ANGGOTA KOPERASI JAGUNG DI DISTRIK MUHANGA, RWANDA - Felicien Nzamurambaho; Titik Ekowati; Siwi Gayatri (Agric, 2022)
This study analyzed farmers’ income between members and non-members of agricultural cooperatives in Muhanga District, Rwanda. The research used a descriptive design based on quantitative approaches; 60 cooperative members and 60 non-cooperative members which were maize farmers selected randomly in the study, plus 6 local leaders and staff of Tuzamurane Cyeza Cooperative who were used as key informants. Data collection tools were questionnaires and interviews. The collected data were analyzed by income and the independent sample t-test analysis to measure farmers’ income between members and non-members of the cooperative. The findings showed that Tuzamurane Cyeza Cooperative provided services such: as easy access to credit, easy access to agricultural inputs, and acquisition of new technology and helped farmers to increase income from the cooperative. The results from the calculation indicated that the mean income of maize farmers who are members of the cooperative (Group 1), 366420 RWF is greater than the mean income of maize farmers who are non-members of the cooperative (Group 2), 137151RWF; (1RWF=14.04IDR). Further, the value of Sig. (0.047) which less than 0.05 was a good indicator that the variance in incomes of maize farmers who are members of the cooperative and non-members of the cooperative was significantly different. Our findings concluded that agricultural cooperatives’ membership contributed to expanding access to markets, and people need to unite themselves in cooperatives because they play a crucial role in reducing poverty, improving food security, and generating employment opportunities.